The constitution of the Earth : The internalization of constitutional law and the constitutionalization of international law - Landa Arroyo, César (2022)
The Constitution of the Earth is presented as a response to contemporary global challenges. Thus, it analyzes how the evolution of constitutional law in Peru since 1979 and its openness to international treaties have strengthened the country's constitutional democracy. The globalization of law has allowed constitutional principles, such as the protection of fundamental rights and the separation of powers, to become universal standards. However, these principles must be adapted to the local and cultural realities of each nation, allowing for the creation of a global legal framework that addresses issues such as extreme poverty, inequality, mass migration, and environmental sustainability. In this way, the Constitution of the Earth promotes mandatory dialogue between national and international legal systems, recognizing the importance of cooperation and coordination in the protection of human rights. This approach seeks to complement, not replace, national regulations with international standards, especially in contexts of severe human rights violations. The Constitution of the Earth is nothing more than a proposal to modernize and unify constitutional and international law, facing current challenges with an integrated and global approach. This legal framework seeks to promote just, peaceful, and inclusive societies, respecting both cultural diversity and the universal principles of democracy and human rights.